Effectiveness of Intramuscular Ketamine as an Adjunct to Standard Care for Reducing Emergence Agitation in Nasal Surgery Patients: Intramuscular Ketamine for Emergence Agitation in Nasal Surgery - Tariq, Amina; Javaid, Kashmala; Khan, Balaj; Khan, Waseem; Nizam, Saira; Raza, Ali (Pakistan Journal of Health Sciences, 2024)
As patients awaken from general anesthesia, they experience restlessness and bewilderment known as emergence agitation. Contributory factors for Emergence agitation include smoking, inhalational anesthetic usage, particular surgical procedures, being young, and being a member of the male population. Objective: To examine the frequency and severity of anxiety attacks in patients having nasal surgery and to assess how well intraoperative ketamine and placebo reduced the incidence of EA. Methods: This study was conducted at Bacha Khan Medical Complex in Swabi. Seventy patients undergoing nasal surgery were divided into two groups in a double-blind trial. One group received intramuscular ketamine, while the other group received saline. A standardized agitation scale measured the incidence and severity of postoperative agitation. The statistical software SPSS for Windows (version 28.0; IBM Corporation) was used to conduct the analysis. Results: Just 5% of patients in the ketamine group experienced EA, compared to 56.3% in the saline group (p ≤ 0.001). The risk of getting EA was 96.7% lower in those on ketamine. Also had much less discomfort following surgery (p < 0.001). Additionally, they reported much less discomfort following surgery (p <0.001). There were no significant differences in postoperative nausea and vomiting across the groups. Conclusions: After nasal operations, intramuscular ketamine administered after the procedure was quite successful in avoiding EA. Although total prevention of EA is difficult, risk factors can greatly lower the incidence of EA. Longer procedures, OSRP surgeries, and ASA II physical condition were the primary risk elements for EA.